Review of Development Activity in Uttar Pradesh 1966-67 Government of Uttar Pradesh - Planning Commission (Planning Commission, 1966)
The year was not favourable for crop production due to extreme drought conditions prevailing in the State. 1.1. Seed saturation—The total quantity of registered seed distributed during the year was 23,768 quintals to Khand Beej Sahayaks and 1,18,888 quintals to Gram Beej Sahayaks against the distribution of 8,624 quintals ,to Khaud Beej Sahayaks and 46,056 quintals to Gram Beej Sahayaks in the corresponding period last year. This shows great improvement in the distribution of registered seed during the year 1966-67. the maximum distribution of registered seed was in Bareilly region whereas in Jhansi region the performance was rather poor. It appears that the targets for distribution of certified seed were not fixed for different regions.
Community Development Department Government of Uttar Pradesh